Revitalization Of The Role and Function Of Intelligence in Indonesia - Halomoan Freddy Sitinjak Alexandra; Parluhutan Sagala; Arief Fahmi Lubis; Yogi Nugroho (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
Intelligence is the knowledge, organization, and activities related to formulating policies, national strategies, and decision-making based on analyzing information and facts collected through work methods for early detection and warning to prevent, deter, and overcome threats to national security. Therefore, for accuracy in reading world political trends and other dimensions in the context of very rapid world change, the role of intelligence is crucial, especially in analyzing emerging threats (current threat trends) and formulating appropriate, contextual, and predictive strategies. These strategies are essential in responding to challenges in times that are changing and relatively uncertain (uncertain periods and conditions).